Understanding the Strategies to Overcome Phosphorus–Deficiency and Aluminum–Toxicity by Ryegrass Endophytic and Rhizosphere Phosphobacteria - Barra, Patricio J.; Viscardi, Sharon; Jorquera, Milko A.; Duran, Paola A.; Valentine, Alexander J.; de la Luz Mora, María (Frontiers in Microbiology, 2018)
Phosphobacteria, secreting organic acids and phosphatases, usually favour plant performance in acidic soils by increasing phosphorus (P) availability and aluminum (Al) complexing. However, it is not well known how P‒deficiency and Al‒toxicity affect the phosphobacteria physiology. Since P and Al problems often co-occur in acidic soils, we have therefore proposed the evaluation of the single and combined effects of P‒deficiency and Al‒toxicity on growth, organic acids secretion, malate dehydrogenase (mdh) gene expression and phosphatase activity of five Al‒tolerant phosphobacteria previously isolated from ryegrass. These phosphobacteria were identified as Klebsiella sp. RC3, Stenotrophomona sp. RC5, Klebsiella sp. RCJ4, Serratia sp. RCJ6 and Enterobacter sp. RJAL6. The strains were cultivated in mineral media modified to obtain i) high P in absence of Al‒toxicity, ii) high P in presence of Al‒toxicity, iii) low P in absence of Al‒toxicity, and iv) low P in presence of Al‒toxicity. High and low P were obtained by adding KH2PO4 at final concentration of 1.4 mM and 0.05 mM, respectively. To avoid Al precipitation, AlCl3 x 6H2O was previously complexed to citric acid (sole carbon source) in concentrations of 10 mM. The secreted organic acids were identified and quantified by HPLC, relative mdh gene expression was determined by qRT-PCR and phosphatase activity was colorimetrically determined using p-nitrophenyl phosphate as substrate. Our results revealed that although a higher secretion of all organic acids was achieved under P‒deficiency, the patterns of organic acids secretion were variable and dependent on treatment and strain. The organic acid secretion is exacerbated when Al was added into media, particularly in the form of malic and citric acid. The mdh gene expression was significantly up-regulated by the strains RC3, RC5 and RCJ6 under P‒deficiency and Al‒toxicity. In general, Al‒tolerant phosphobacteria under P deficiency increased both acid and alkaline phosphatase activity with respect to the control, which was deepened when Al was present. The knowledge of this bacterial behavior in vitro is important to understand and predict the behavior of phosphobacteria in vivo. This knowledge is essential to generate smart and efficient biofertilizers, based in Al‒tolerant phosphobacteria which could be expansively used in acidic soils.